Single Nucleotide Polymorphism of IL1B Gene (rs16944) in a Sample of Rheumatoid Arthritis Iraqi Patients - Mahmood, Aseel S.; Al-Kazaz, Abdul-Kareem A.; Ad'hiah, Ali H. (Iraqi Journal of Science, 2018)
Cytokines play a prominent role in etiology and pathogenesis of rheumatoid arthritis (RA), and one of these cytokines is interleukin-1β (IL-1β). The association between IL1B gene single nucleotide polymorphism (SNP: rs16944) and rheumatoid arthritis (RA) in a sample of Iraqi patients was investigated. Fifty-one RA patients (21 males and 30 females) were enrolled and their age range was 20 - 63 years (44.9 ± 1.5 years). In addition to patients, 45 apparently healthy control subjects were also enrolled in the study. They matched patients for ethnicity (Iraqis), gender (14 males and 31 females) and age (41.3 ± 1.3 years). Analysis of Hardy-Weinberg equilibrium (HWE) in RA patients and controls revealed that the IL1B genotypes were consistent with the equilibrium, and no significant differences (p > 0.05) were observed between the observed and expected genotype frequencies. Inspecting IL1B genotype and allele frequencies in RA patients and controls revealed that there were no significant variations between these frequencies, although a decreased frequency of T allele (67.7 vs. 73.3%) and an increased frequency of C allele (32.3vs. 26.7%) were observed in patients compared to controls. In conclusion, the results are in favor of no association between IL1B gene SNP (rs16944) and RA in Iraqi population.